2015
DOI: 10.1021/acs.iecr.5b03427
|View full text |Cite
|
Sign up to set email alerts
|

Facile Route for Fuel Desulfurization Using Generated Superoxide Ion in Ionic Liquids

Abstract: In this study, a novel desulfurization method was conducted using the superoxide ion (O 2 •−) generated chemically in four ionic liquids (ILs): 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, N-methoxyethyl-N-methylmorpholinium bis(trifluoromethylsulfonyl)imide, 1-(2-methoxyethyl)-1-methylpiperidinium tris(pentafluoroethyl)trifluorophosphate, and 4-(2-methoxyethyl)-4-methylmorpholinium tris(pentafluoroethyl)trifluorophosphate. Remarkably, it was found that O 2•− can convert the sulfur compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…These results indicated that the conversion of BT was easier than that of DBT, and this difference was attributed to two factors, i.e., the electron density around the sulfur atom and the steric hindrance. This is in agreement with a recent study conducted on the conversion of thiophene and 2-methylthiophene using O 2 •– . The electron densities around the sulfur atoms in BT and DBT were calculated by Otsuki et al (2000) as 5.739 and 5.758, respectively .…”
Section: Resultssupporting
confidence: 90%
“…These results indicated that the conversion of BT was easier than that of DBT, and this difference was attributed to two factors, i.e., the electron density around the sulfur atom and the steric hindrance. This is in agreement with a recent study conducted on the conversion of thiophene and 2-methylthiophene using O 2 •– . The electron densities around the sulfur atoms in BT and DBT were calculated by Otsuki et al (2000) as 5.739 and 5.758, respectively .…”
Section: Resultssupporting
confidence: 90%
“…Remarkably, it was found that O2 − destroyed close to 90% of the thiophene in [EDMPAmm][TFSI] at ambient conditions. This result was in good agreement with the findings of recent studies (Chan et al, 2008;Hayyan et al, 2015b;Hayyan et al, 2016b). Chan et al (2008) zation process.…”
Section: Destruction Of Thiophenesupporting
confidence: 93%
“…Hence, they have been used to desulfurize fuels by various methods, including extraction (Ferreira et al, 2014;Lu et al, 2014) and oxidative desulfurization (Jiang et al, 2014;Lü et al, 2014). Recently, our group reported the possibility of using O2 − generated in ILs to destroy chlorinated hydrocarbons and sulfur compounds (Hayyan et al, 2012f;Hayyan et al, 2012e;Hayyan et al, 2015b;Hayyan et al, 2016b;AlNashef et al, 2013). Therefore, it also was worthwhile to explore using O2 − to destroy sulfur compounds in one of the studied ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore ILs are highly tunable and can be designed with a specific task in mind, hence the term 'designer solvents' that is sometimes used to describe them [7]. For this reason ILs have been explored for a wide range of applications including catalysis [8,9], electrochemistry [10,11], fuel cells [12] and separation processes [13].…”
Section: Introductionmentioning
confidence: 99%